A pragmatic assessment of the British Thyroid Association "U classification" of thyroid nodules with a focus on their follow-up. Issue 6 (June 2020) - Arambewela, M.H.; Wijesinghe, A.M.; Randhawa, K.; Bull, M.; Wadsley, J.; Balasubramanian, S.P.
Abstract : AIM: To assess the predictive value of the U classification and the significance of follow-up ultrasound in those managed conservatively. MATERIALS AND METHODS: A retrospective observational study was carried out among 1, 465 patients who underwent thyroid ultrasound in 2016 at a teaching hospital in UK. Details regarding U classification of nodules, cytology, histology in patients who underwent surgery, and follow-up ultrasound in those managed conservatively were obtained. RESULTS: Thyroid surgery was performed in 129 patients of which malignancy was seen in 35 (27.1%). The proportion of patients with cancer in U1–U5 categories were 0%, 13.6%, 30.4%, 40%, and 100%, respectively (Fisher's exact test p =0.001). There was no significant difference in U stage, cytology, or histology between incidental and symptomatic nodules. Among patients who did not undergo surgery 5% of U1, 14.6% of U2, 75% of U3, and 71.4% of U4 underwent repeat ultrasound. Radiological progression in nodule size was seen in 4.2% of U1, 1.9% of U2, 0% of U3, and 40% of U4 nodules at median duration of 306, 439, 274, and 748 days, respectively. CONCLUSIONS: U classification is reliable in risk-stratifying thyroid nodules. Patients with benign nodules without high-risk features do not require follow-up. The interval between scans in patients with indeterminate nodules can be extended to a period of 6–12 months. Highlights: The British Thyroid Association "U classification" is reliable in stratifying thyroid nodules. Benign nodules without high risk clinical features do not warrant follow up. Interval scans for indeterminate nodules without high risk features, can be extended to a period of 6–12 months. Nodules should not be managed differently based on incidental detection.